Quantitative Shotgun Proteomics Unveils Candidate Novel Esophageal Adenocarcinoma (EAC)-specific Proteins - O'Neill, J Robert; Pak, Hui-Song; Pairo-Castineira, Erola; Save, Vicki; Paterson-Brown, Simon; Nenutil, Rudolf; Vojtěšek, Bořivoj; Overton, Ian; Scherl, Alex; Hupp, Ted R (Molecular and cellular proteomics, 2017)
Esophageal cancer is the eighth most common cancer worldwide and the majority of patients have systemic disease at presentation. Esophageal adenocarcinoma (OAC), the predominant subtype in western countries, is largely resistant to current chemotherapy regimens. Selective markers are needed to enhance clinical staging and to allow targeted therapies yet there are minimal proteomic data on this cancer type. After histological review, lysates from OAC and matched normal esophageal and gastric samples from seven patients were subjected to LC MS/MS after tandem mass tag labeling and OFFGEL fractionation. Patient matched samples of OAC, normal esophagus, normal stomach, lymph node metastases and uninvolved lymph nodes were used from an additional 115 patients for verification of expression by immunohistochemistry (IHC).Over six thousand proteins were identified and quantified across samples. Quantitative reproducibility was excellent between technical replicates and a moderate correlation was seen across samples with the same histology. The quantitative accuracy was verified across the dynamic range for seven proteins by immunohistochemistry (IHC) on the originating tissues. Multiple novel tumor-specific candidates are proposed and EPCAM was verified by IHC.This shotgun proteomic study of OAC used a comparative quantitative approach to reveal proteins highly expressed in specific tissue types. Novel tumor-specific proteins are proposed and EPCAM was demonstrated to be specifically overexpressed in primary tumors and lymph node metastases compared with surrounding normal tissues. This candidate and others proposed in this study could be developed as tumor-specific targets for novel clinical staging and therapeutic approaches.
Keywords: senioři; proteomika; Male; Female; Adenocarcinoma; Proteomics; Aged; Middle Aged; nádory jícnu; adenokarcinom; mužské pohlaví; ženské pohlaví; Adult; nádorové proteiny; Esophageal Neoplasms; dospělí; nádorové biomarkery; lidé středního věku; Biomarkers, Tumor; lidé; Humans; Neoplasm Proteins